The Flame Characteristics of Diesel Fuel Blend with Kepuh (Sterculia Foetida) Biodiesel - Prasetiyo, Dani Hari Tunggal; Ilminnafik, Nasrul; Junus, Sallahudin (Universitas Negeri Malang, 2019)
Kepuh biodiesel fuel (sterculia foetida) is an alternative fuel that can be used to replace fossil fuel. Diesel fuel is performed to determine the laminar flame speed of combustion and high flame by adding biodiesel kepuh volume of 10%, 20%, 30%. The purpose of this study was to study the effect of biodiesel and the effect of bunsen burners on the laminar flame speed of combustion and flame height. Bunsen burner is made of copper and stainless steel. Testing of flame characteristics were carried out by heating the mixture of fuel and air at temperature of 200oC. The purpose of heating the air is to prevent cooling when mixed with fuel. The mixture of fuel and air flowed into the mixing chamber and bunsen burner. The mixture of fuel and water flows into the mixing chamber and bunsen burner to form a fire. Flame images were recorded using a high speed fuji film camera with a speed of 480 fps with a resolution of 224x168. The test results were analyzed by measuring the angle and height of the flame using the freeware imageJ program. The results of the B10 (diesel oil without the addition of biodiesel) fuel mixture test using copper bunsen burner produced a maximum laminar flame speed of 23.6264 cm / s at φ = 0.8. The highest value of the B30 fuel mix flame (30% full biodiesel + 70% diesel oil) produces a maximum flame value using a stainless steel bunsen burner with a value of 25,417 mm at φ = 1.2. The results showed that B10 in copper bunsen burner had the highest laminar burn rate. The composition of the fuel and bunsen burner affects the combustion characteristics and flame height.